A Review of Clinical Poster Presentations at the Sixth Biennial Pediatric Anesthesia Neurodevelopment Assessment (PANDA) Symposium. Issue 1 (January 2019) - Haché, Manon; Hansen, Tom G.; Graham, Ruth; Sinton, Jamie W.; Adams, Phillip S.; Garber, Carol; Maxwell, Lynne; Pinyavat, Teeda
Abstract : Clinical researchers studying the long-term neurocognitive effects of anesthetic and sedative agents on children continue to struggle with identifying a phenotype for anesthetic neurotoxicity, the window of vulnerability, and the toxicity threshold in terms of concentration and duration. The Sixth Biennial Pediatric Anesthesia Neurodevelopment Assessment (PANDA) symposium at Columbia University included a moderated poster presentation session where 4 investigators presented their latest contributions to the landscape of clinical anesthetic neurotoxicity research. A lack of standardization in the design of clinical studies in terms of age at exposure, duration and type of exposure, and outcome measures assessed were highlighted by all the investigators. Suggestions for the future direction of clinical trials included the implementation of more consistent study parameters and the employment of standardized neurocognitive testing and imaging before and after exposure to general anesthesia. Presentations covered a broad range of topics including the valid translation of preclinical studies to human subjects, the quantification of real-world exposures to anesthetic and sedative medications, and possible alternatives to these exposures.